Criminal sanctions against perpetrators of animal abuse from the perspective of islamic criminal law (Case study in the City of Medan) - Nadila, Nadila; Sukiati, Sukiati (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
Animal abuse is a crime. This study aims to examine how criminal sanctions for perpetrators of animal abuse crimes from the perspective of positive criminal law and Islamic criminal law. This study is an empirical legal study by exploring two data sources, namely primary and secondary data sources. Data were obtained through interviews and documentation. The results of this study aim to examine the phenomenon of animal abuse that occurs in the city of Medan and the criminal sanctions for perpetrators of animal abuse from the perspective of positive law and Islamic criminal law. In the perspective of positive criminal law, sanctions for perpetrators of animal abuse are regulated in Article 302 of the Criminal Code. In this article, the criminal law sanction is imprisonment for up to nine months or a fine, depending on the severity of the action. This sanction aims to punish the perpetrator while providing a deterrent effect. Meanwhile, in Islamic criminal law, animal abuse is included in the ta’zir crime, which reflects a violation of Allah’s rights. Ta’zir sanctions are determined by local authorities to provide a deterrent effect and educate perpetrators to love animals more. In conclusion, both legal systems positive and Islamic acknowledge animal abuse as a serious moral and legal offense. Sanctions not only aim to punish but also to prevent recurrence through deterrence and education. Effective enforcement of these sanctions is essential to fostering empathy and accountability within society toward animal welfare. Both legal systems recognize animal abuse as a serious offense and underline the need for sanctions to deter and reform offenders.